On interaction of arginine, cysteine and guanine with a nano-TiO2 cluster. (June 2020) - Sai Phani Kumar, V.; Verma, Manju; Deshpande, Parag A.
Graphical abstract: Highlights: Interaction of biomolecules with titania probed using DFT calculations. Arginine, cystine and guanine tested as representative biomolecules. Energetically favored interactions revealed with a nano-titania cluster. Functional groups on biomolecules responsible for interactions identified. Abstract: Nanoscopic properties of TiO2 augmented with its physicochemical properties and biocompatibility make it a material interest in the biomedical field. Efficient methods to design of such materials require a thorough understanding of associated nano-bio interfaces. In the present study, density functional theory calculations were performed to study the interactions of arginine, cysteine and guanine with a nano-TiO2 cluster. Different configurations were sampled for the adsorption of arginine, cysteine and guanine to probe the nano-bio interface via the interaction of various functional groups present on biomolecules. Adsorption energies for arginine, cysteine and guanine were in a range of −25.0 to −57.6, −12.1 to −29.6 and −45.6 to −58.7 kcal/mol, respectively. From the change in adsorption energies and free energies, interaction of amino acids with carboxylic (COOH), thiol (SH) and amine (NH2 ) groups while the interaction of the nucleobase via O bonded to C and N of purine ring was found to be essential for thermodynamically stable and energetically favorable states. Density of states analysis also disclosed the prominent interactions of the biomolecules with the nano-TiO2 cluster. Decrease in band gaps on adsorption of the biomolecules was a pertinent phenomenon indicating the strong chemical interactions of the biomolecules with the nanoscopic TiO2 chosen for analysis in this study.